Urinary tract infection in young women, with special reference to Staphylococcus saprophyticus. Issue 4 (April 1978) - Gillespie, W A; Sellin, M A; Gill, P; Stephens, M; Tuckwell, L A; Hilton, A L
Abstract : Acute urinary tract infections in young women attending a clinic for sexually transmitted diseases were caused by the same bacteria, in the same proportions, as those that caused infections in women students. Staphylococcus saprophyticus biotype 3 (formerly called Micrococcus subgroup 3) was the commonest organism after coliform bacilli and caused about 30% of the infections. It was uncommon in women over 25 years of age and rarely caused asymptomatic bacteriuria in pregnancy. Most infections, irrespective of the causative organism, started soon after sexual intercourse, but neither the staphylococci nor the other organisms were associated with promiscuity, as judged by numbers of sexual partners or the incidence of sexually transmitted diseases. There was no evidence that the staphylococci were sexually transmitted. The reasons for the virulence of Staph. saprophyticus and its predilection for the urinary tract of young women remain unknown.